The Impact of Using Video Media in Increasing Motivation for Speaking Ability - Siti Julaihah (Jurnal Penelitian)
The purpose of this study was to determine the impact of using video media in increasing the motivation of the cadets' speaking skills. This research was conducted to determine the contribution to the motivation of speaking skills as a result of the use of video media for aircraft engineering cadets. The method used in this research is an experiment in which the research stage is carried out in two cycles. The results of this study indicate dIn the first cycle, it showed an average score of 66.61 which was in the sufficient category, and showed an increase in the second cycle to obtain an average score of 80.88 which was included in the good category. This increase shows the impact of using video media in improving the speaking skills of cadets.